2015
DOI: 10.5415/apallergy.2015.5.4.216
|View full text |Cite
|
Sign up to set email alerts
|

First study of pattern of anaphylaxis in a large tertiary care hospital in Saudi Arabia

Abstract: BackgroundAnaphylaxis is a serious allergic reaction that may cause death. The signs and symptoms of anaphylaxis have not been examined in the Saudi population before.ObjectiveThe present study examined the signs, symptoms, triggers, and demographic patterns of patients treated for anaphylaxis at a large tertiary care hospital in Riyadh, Saudi Arabia.MethodsAll the patients who were prescribed new prescriptions of adrenaline auto-injectors (AAs) between February 1, 2010 and December 31, 2011 were included in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 13 publications
(12 reference statements)
3
19
1
1
Order By: Relevance
“…Our study demonstrated that food anaphylaxis in adults was the most common type, as opposed to drug anaphylaxis seen in reports from Western [18][19][20] and some Asian [21,22] countries. Food was the most common cause of anaphylaxis in prior studies of adults in Singapore [9], China [23], and Saudi Arabia [24], and in the general population in Thailand [25] and Hong Kong [17]. Shellfish was the most common food allergen in our study, echoing findings from Asian countries such as Thailand [25], Taiwan [26], and Hong Kong [17].…”
Section: Discussionsupporting
confidence: 75%
“…Our study demonstrated that food anaphylaxis in adults was the most common type, as opposed to drug anaphylaxis seen in reports from Western [18][19][20] and some Asian [21,22] countries. Food was the most common cause of anaphylaxis in prior studies of adults in Singapore [9], China [23], and Saudi Arabia [24], and in the general population in Thailand [25] and Hong Kong [17]. Shellfish was the most common food allergen in our study, echoing findings from Asian countries such as Thailand [25], Taiwan [26], and Hong Kong [17].…”
Section: Discussionsupporting
confidence: 75%
“…Most of these were employees of the hospital or their dependents. The signs, symptoms and triggers of anaphylaxis from these patients have already been described previously [18].…”
Section: Resultsmentioning
confidence: 73%
“…The mean age was 22.9 years, (2 years to 73 years) SD ± 18.2. Male to female ratio was 48:52 and 54% of the patients were 18 or older.…”
Section: Introductionmentioning
confidence: 97%
“…In a pediatric series, the median age was 1 year (5). In a study from Saudi Arabia, sesame was the third most common trigger of food-induced anaphylaxis (6). According to a multicenter study in Italy (7) by the EpidemAAITO (Associazione Allergologi Immunologi Territoriali e Ospedalieri) consortium, of 351 adults sensitized to various fruits and vegetable, there were five with systemic symptoms to seeds (sesame and sunflower).…”
Section: Epidemiologymentioning
confidence: 99%